Shock Index Is an Effective Predictor of Postpartum Transfusion Requirement in Normal Vaginal Deliveries - Malik, Shamsa; Awan, Aatiqa; Khan, Hina Sultan (Biological and Clinical Sciences Research Journal, 2025)
Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide, particularly in low- and middle-income countries. Traditional vital signs such as heart rate and systolic blood pressure are often insufficient in early recognition of hemodynamic instability due to the physiological adaptations of pregnancy. The shock index (SI), calculated as heart rate divided by systolic blood pressure, has emerged as a promising tool for early detection of postpartum complications. Objective: To evaluate the effectiveness of the shock index in predicting the requirement for postpartum blood transfusion in women undergoing normal vaginal deliveries. Methods: This prospective observational study was conducted at Sir Ganga Ram Hospital, Lahore, from July to December 2024. A total of 240 women who underwent spontaneous vaginal delivery were enrolled. SI was calculated within 15 minutes postpartum, and patients were monitored for 24 hours to identify those requiring blood transfusion. Data were analyzed using SPSS version 26. Logistic regression was used to adjust for confounding variables including age, parity, pre-delivery hemoglobin, and estimated blood loss. Results: Of the 240 participants, 53 (22.1%) required postpartum blood transfusion. SI >0.9 was observed in 61 women (25.4%), of whom 41 (67.2%) required transfusion (p<0.001). Elevated SI was independently associated with transfusion need (aOR: 6.87, 95% CI: 3.32–14.22). Pre-delivery hemoglobin <10 g/dL and estimated blood loss >600 mL were also significant predictors. Conclusion: An elevated shock index (>0.9) is a strong and independent predictor of postpartum transfusion requirement following normal vaginal delivery. SI should be incorporated into routine postpartum monitoring protocols to enable early identification of women at risk and timely intervention.